(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
The work presents the results of exergetic analysis of a reversible chiller providing both cooling and space heating in varying operational modes. The year values of avoidable parts of exergy destruction occurring in each system component are used for the analysis. The outcomes obtained showed that the both inside and outside heat exchangers have the highest priority for improvement revealing more than 718 kW-hr avoidable year exergy destruction within the system.